Some Changes in Chemical Properties Land and Growth of Corn (Zea mays L.) Giving Due Waste Cigarette Paper Factory and Chicken Manure On Ultisol Soil - Albi Abdillah; Kemala Sari Lubis; Mukhlis Mukhlis (Jurnal Agroekoteknologi, 2018)
The solid waste of the factory of wrapper cigarette is generated very much by the factory of wrapper cigarette PT.Pusaka Prima Mandiri. This waste contains calcium carbonate + 70,81% and can increase acidity of Ultisol. The research was to conduct study the utilization of solid waste of the factory of wrapper cigarette and chicken manure to repair soil acidity and nutrient content of Ultisol. Screen house research has been conducted to examine the effect of solid waste of the factory of wrapper cigarette and chicken manure in overcoming acidity and soil nutrient enhancement Ultisol. This research was conducted by randomized block design two (2) factors. The first factor is solid waste of the factory of wrapper cigarette consists of  five (5) doses and the second factor is chicken manure consisting of three (3) doses with three (3) replications. Analysis of soil was conducted at the Laboratory of Oil Palm Research Centerand Soil Chemistry Laboratory ofFaculty of Agriculture, University of North Sumatra. Parameters observed include soil pH, Al(exch), P-available, plant height and dry weight of crown and root maize. The results showed that the solid waste ofthe factory of wrapper cigarette can decrease acidity of Ultisol and increase increase the plant height and dry weight of the crown. Chicken manure can decrease acidity of Ultisol. The solid waste of the factory of wrapper cigarette has the potential to decrease Al(exch) and meet the availability of P in the soil.